Hubungan Umur, Paritas Dan Pendidikan Ibu Dengan Kejadian Intra Uterin Fetal Death (IUFD) Di Ruang Bersalin Di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin Tahun 2013 - Akhmad Mahyuni; Amelia Pradita; Rahmatul Jannah; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Intra Uterin Fetal Death (IUFD) is the death of a fetus in pregnancy before childbirth process occurs at 28 weeks gestation or fetal weight of over 1000 grams. This research aims to know the relationship between age, parity and maternal education with intra uterin fetal death (IUFD) in maternity RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2013. This research use analytic survey methods research design of Case Control. The population in this research is the whole birthing mothers in the maternity RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2013 as 1624 people. The sample in this research is the mother experiencing intra uterin fetal death as many as 49 people as case and mothers who experienced no intra uterin fetal death as many as 49 people as a control. Results of the study showed the majority of mothers with age not at risk as many as 52 people (53.1%), the majority of mothers have parity is not secure as many as 52 people (53.1%) and the majority of mothers with primary education as many as 42 people (42,9%) is. Results of statistical tests with chi-square showed that age brings the value of ρ = 0.000, parity is ρ = 0.002 and education ρ = 0,126 with α = 0.05, which means there is relationship of mother's age and parity occurrences intra uterin fetal death in maternity RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2013. There is no relationship education mother with the incident of intra uterin fetal death at the provincial RSUD Dr. H. Moch Ansari Saleh Banjarmasin in 2013.